Supporting factors for labor productivity in Indonesia - Muhammad Amir Arham; Fitri Hadi Yulia Akib (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
Indonesia's investment attractiveness is still weak compared to other ASEAN countries; one of the reasons is the low labor productivity. On this basis, this study aims to find out what factors are dominantly driving labor productivity in Indonesia statistically, as well as the right policy model to encourage labor productivity, bringing Indonesia a high-income country. The analytical method used in this study is panel data regression analysis, 2014 - 2018 period, covering 34 provinces in Indonesia. The study suggests that fiscal policy through general allocation fund (DAU) or transfers signifies increasing labor productivity, while special allocation fund (DAK) does not. Economic factors such as labor costs, the contribution of the agricultural sector, and economic openness can increase labor productivity, while industrial sector share has no effect. Social factors measured by the education level of general secondary schools and life expectancy (health) affect labor productivity enhancement; it is different from a vocational school. Consequently, the number of unemployed vocational school graduates is high.